Variation in emperor goose (Anser canagicus) body mass at the geographic extremes of their wintering range - Scholl, Sophie, author; Aubry, Lise, advisor; Thomas, Robyn, committee member (Colorado State University. Libraries, 2025)
The emperor goose (Anser canagicus) is a waterfowl species that is endemic to the Bering Sea and holds great ecological, recreational, and cultural value. Emperor geese are unique in their wintering behaviors as they migrate only slightly south of their summer breeding grounds in the Yukon-Kuskokwim Delta to non-breeding wintering grounds that are at relatively high latitudes along the Aleutian Islands, Alaska Peninsula, and the Kodiak Archipelago. Recent declines in emperor goose populations brings to light the importance of developing a more comprehensive understanding of emperor goose ecology, with a particular focus on understanding previously understudied aspects of their wintering ecology. This study explores differences of body mass as a proxy for individual fitness between two wintering sites that represent the geographic extremes of the emperor goose wintering distribution: Shemya Island and the Kodiak Archipelago. A significant difference in body mass between Kodiak and Shemya was observed amongst all adult geese, specifically amongst female adults, with geese on Shemya having lower body mass than the geese on Kodiak in these demographic groups. Additionally, it was observed that variation in body mass among emperor geese could be explained by additive effects of age class, sex, and field site. These findings indicate that differences in environmental conditions, food source availability, and migration distance to the different wintering sites between Shemya and Kodiak could explain why some demographic groups of emperor geese displayed significantly lower body masses, and therefore lower fitness, at Shemya (i.e. longer winter migration, extreme environment, lower access to protein-rich food). Understanding the wintering ecology of emperor geese and dedicating more time and resources to explaining variability in fitness experienced by emperor geese at their wintering sites is critical for understanding how to best move forward with conservation and management strategies that prevent further population declines.
Keywords: emperor goose; Anser canagicus; wintering ecology; Shemya Island; Kodiak Archipelago; fitness